Formation of santri discipline in Darul Mukhlisin Serdang Bedagai Islamic boarding school - Rahmat Ramadhan Nasution (Yayasan Bayt Shufiya Nusantara, 2024)
This study aims to examine the process of forming the discipline character of students at Darul Mukhlisin Islamic Boarding School. The main focus of this study is how the Kulliyatul Mu'allimin Al-Islamiyah (KMI) curriculum is adopted and implemented as part of the pesantren's responsibility in shaping santri discipline through daily activities. The method used is a field study with a qualitative approach. Primary data were obtained through in-depth interviews with mu'allim/mu'allimah, administration, and santri/students of Darul Mukhlisin Islamic Boarding School, while secondary data were collected from books, journal articles, theses, and other relevant scientific literature. Triangulation techniques are used in the data analysis process to ensure the validity of the findings. The results showed that the formation of santri disciplinary character is implemented through worship habits, da'wah activities, as well as continuous advice and supervision. The KMI curriculum provides a systematic framework for pesantren in instilling disciplinary values through consistent rules, activity schedules, and habituation. However, challenges still arise, especially when santri are outside the pesantren during the vacation period, which often relaxes the discipline that has been formed. Therefore, the sustainability of coaching and supervision is key in maintaining the disciplinary character of santri on an ongoing basis.